(untitled) (ModaPalavra e-periódico, 2014)
The social-environmental practices conform as a fundamental premise to the planet’s life quality. Observing the fashion as a language of communication and possible configure it as a tool that allows the practice and the ethical awareness sustainable. This present project aims to unite social-environmental principles to the project methodology of fashion design. The result suggests the creation of garments that are aimed at reducing the environmental impacts and social inclusion of classes or disadvantaged groups in the process of drawing up of a collection of fashion. In this sense stating the viability of marketing a quality product that meets the needs and wishes of the public delimited.